2015
DOI: 10.2174/1570162x13666150311164201
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of HIV-1 Tat Neurotoxicity via CDK5 Translocation and Hyper-Activation: Role in HIV-Associated Neurocognitive Disorders

Abstract: The advent of more effective antiretroviral therapies has reduced the frequency of HIV dementia, however the prevalence of milder HIV associated neurocognitive disorders [HAND] is actually rising. Neurodegenerative mechanisms in HAND might include toxicity by secreted HIV-1 proteins such as Tat, gp120 and Nef that could activate neuro-inflammatory pathways, block autophagy, promote excitotoxicity, oxidative stress, mitochondrial dysfunction and dysregulation of signaling pathways. Recent studies have shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 158 publications
(181 reference statements)
1
37
0
1
Order By: Relevance
“…Consistent with previous findings by others and us that HIV-1 Tat increases neuronal Aβ generation (Rempel and Pulliam, 2005; Giunta et al, 2009; Aksenov et al, 2010; Chen et al, 2013) and tau phosphorylation (Giunta et al, 2009; Fields et al, 2015), we demonstrated in SH-SY5Y human neuroblastoma cells over-expressing wild-type AβPP that HIV-1 Tat treatment significantly increased levels of secreted Aβ 1–40 and Aβ 1–42 (Figure 1A). The HIV-1 Tat concentration used here is consistent with the Tat levels (>4000 pg/ml) measured in CSF of infected individuals regardless of viral load (Johnson et al, 2013).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous findings by others and us that HIV-1 Tat increases neuronal Aβ generation (Rempel and Pulliam, 2005; Giunta et al, 2009; Aksenov et al, 2010; Chen et al, 2013) and tau phosphorylation (Giunta et al, 2009; Fields et al, 2015), we demonstrated in SH-SY5Y human neuroblastoma cells over-expressing wild-type AβPP that HIV-1 Tat treatment significantly increased levels of secreted Aβ 1–40 and Aβ 1–42 (Figure 1A). The HIV-1 Tat concentration used here is consistent with the Tat levels (>4000 pg/ml) measured in CSF of infected individuals regardless of viral load (Johnson et al, 2013).…”
Section: Resultssupporting
confidence: 93%
“…High concentrations of HIV-1 Tat levels (>4000 pg/ml) were observed in CSF of HIV infected individuals regardless of viral load (Johnson et al, 2013). HIV-1 has been shown to increase neuronal Aβ generation (Rempel and Pulliam, 2005; Giunta et al, 2009; Aksenov et al, 2010) and tau phosphorylation (Giunta et al, 2009; Fields et al, 2015). HIV-1 Tat enters neurons rapidly by receptor-mediated endocytosis with the assistance of low-density lipoprotein receptor-related protein (LRP-1) (Liu et al, 2000; Vendeville et al, 2004; King et al, 2006; Deshmane et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Next we measured the levels of EndoB1, also referred as BIF1, (Figure 2A, D) since this molecule has been shown to regulate autophagy via interactions with the UV radiation resistance-associated gene (UVRAG)/Beclin1 complex (Wong et al , 2011). Moreover, EndoB1 is a substrate of CDK5 (Wong et al , 2011), which is hyper-activated by Tat (Fields et al , 2015b; Lee et al , 2013), and as we have shown, sunitinib modulates CDK5 activation (Wrasidlo et al , 2014). In vehicle-treated cells, challenge with Tat resulted in reduced EndoB1 compared to non-Tat-challenged cells (Figure 2A, D).…”
Section: Resultsmentioning
confidence: 81%
“…Among other pathways, Tat-mediated neurodegeneration has been associated with hyper-activation of CDK5 and accumulation of increased Tau phosphorylation (Fields et al , 2015b; Lee et al , 2013). Consistent with this notion and similar to the biochemical findings in Figure 5, we found that compared to non-tg mice (treated with vehicle or sunitinib), vehicle treated Tat tg mice displayed increased CDK5, p35 and pTau immunoreactive in the cortex (Figure 7A-D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation